2014
DOI: 10.1080/23248823.2014.969005
|View full text |Cite
|
Sign up to set email alerts
|

How personal parties change: party organisation and (in)discipline in Italy (1994–2013)

Abstract: The rise of personal parties is one of the most relevant and innovative political phenomena to emerge from the Italian Second Republic. During the 1990s, Forza Italia presented a new type of party political organisation where personalisation, professionalisation and centralisation represented the keys to success that led Silvio Berlusconi to three general election victories, and that were soon variously taken up by both the centre-right and centre-left coalitions. Yet, two decades after Berlusconi entered poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
(19 reference statements)
0
6
0
1
Order By: Relevance
“…One of the most significant innovations made by the Italian Democratic Party was the use of primaries to nominate candidates to Parliament, which were called 'parlamentarie'. These took place on 29-30 December 2013 to choose about 85% (782 out of 918) of PD candidates for the two parliamentary houses, with the remaining candidates directly nominated by the PD leader (Musella, 2014a).…”
Section: The Iron Law Of Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most significant innovations made by the Italian Democratic Party was the use of primaries to nominate candidates to Parliament, which were called 'parlamentarie'. These took place on 29-30 December 2013 to choose about 85% (782 out of 918) of PD candidates for the two parliamentary houses, with the remaining candidates directly nominated by the PD leader (Musella, 2014a).…”
Section: The Iron Law Of Leadershipmentioning
confidence: 99%
“…Yet, it remains to be investigated to what extent the party leader is able to realize political programmes, in a context in which personalization, while leading to a reinforcement of the figure of party leaders, also challenges party cohesion. With respect to the Italian case, it has to be observed that strong and visible party leaders have coexisted with high levels of party indiscipline, thus showing that the autonomy of the leader in the party's internal decision-making procedures is not the same thing as the ability to direct MPs (Musella, 2014b). Although after Tangentopoli the rise of the personal party identified with Forza Italia has implied both the creation of a new model of party organization and the adoption of a more plebiscitary idea of political representation (Calise, 2010(Calise, [2000), two decades later the personalization of politics has shown another side, as it has involved not simply the higher levels of a party's organization, but all levels.…”
Section: The Party Leader In Governmentmentioning
confidence: 99%
See 1 more Smart Citation
“…27 El politólogo Fortunato Musella analisiza la personaficación en los partidos políticos. En la ultima decada del siglo pasado se caracterizo por el surgimiento de los «partidos personales es uno de los fenómenos políticos más relevantes e innovadores» (Musella, 2014). 28 No entraremos aquí a valorar la legitimidad de las decisiones con mayorías o de escasas mayorías.…”
Section: Antecendentesunclassified
“…Moreover, all parliamentary groups have exhibited a high level of lack of discipline (see the very good account by Musella [2014]). But despite some mergers -for instance, the one between the Left Democrats and the Margherita (Daisy, made up mostly of former Christian Democrats turned Popolari) that in 2007 formed the Democratic Party -overall the Italian party system has not been restructured at all.…”
Section: The Party System: Structure and Competitionmentioning
confidence: 99%